Stable Fourth-Order Stream-Function Methods for Incompressible Flows with Boundaries (Journal of Computational Mathematics, 2009)
Fourth-order stream-function methods are proposed for the time dependent, incompressible Navier-Stokes and Boussinesq equations. Wide difference stencils are used instead of compact ones and the boundary terms are handled by extrapolating the stream-function values inside the computational domain to grid points outside, up to fourth-order in the no-slip condition. Formal error analysis is done for a simple model problem, showing that this extrapolation introduces numerical boundary layers at fifth-order in the stream-function. The fourth-order convergence in velocity of the proposed method for the full problem is shown numerically.
Keywords: Incompressible flow; Stream-function formulation; Finite difference methods.